Additions to the knowledge of the pollen morphology of some Fabaceae from Cerrado forest patches of Brazil - Soares, Eduardo Lopes [UNESP] (2020)
This study presents the pollen morphology of 11 Brazilian native species and one variety of Caesalpinioideae and Detarioideae (Fabaceae) from forest patches of São Paulo, Brazil. The aim of this research is to expand the morphological knowledge of the species of these subfamilies, contributing to the taxonomic study and conservation of these species in the forest area. The pollen grains were acetolyzed, measured, described qualitatively and illustrated using light microscopy and scanning electron microscopy. Differences in pollen unit (tetrads or monads), size (small to large), amb (circular to triangular), shape (oblate to prolate), details of the polar area (very small to large), position of apertures (angulaperturate, planaperturate, subplanaperturate, or fossaperturate), type of endoapertures (lolongate, circular, or lalongate) and exine ornamentation (psilate, scabrate, microreticulate, or reticulate heterobrochate) aid in the differentiation of pollen grains of the analyzed species. In this study, the metric variables related to the apertures assist in the quantitative separation of the species (multivariate analysis), and these variables, together with the qualitative data, contribute to affirm the eurypalynous character of the subfamilies Caesalpinioideae and Detarioideae.